Using spoken dialogue technology for L2 speaking practice: what do teachers think?. Issue 5 (4th July 2022) - Timpe-Laughlin, Veronika; Sydorenko, Tetyana; Daurio, Phoebe
Abstract: Often, second/foreign (L2) language learners receive little opportunity to interact orally in the target language. Interactive, conversation-based spoken dialog systems (SDSs) that use automated speech recognition and natural language processing have the potential to address this need by engaging learners in meaningful, goal-oriented speaking practice. However, these technology-based learning tools are often developed without input from teaching professionals. As part of a larger development effort, this study examined English as a second language (ESL) teachers' perceptions regarding SDS-based speaking tasks, addressing the following research questions: (a) What do teachers think about the SDS-based tasks? (b) How would they use them in the context of their English instruction? Overall, 16 ESL instructors in an intensive English program in the United States were asked to interact with four SDS-based speaking tasks designed to elicit specific linguistic phenomena (e.g. making requests; wh-questions). The teachers completed a survey after each task to gauge their user experience, level of engagement, and perceptions of the usefulness of the tasks for their teaching contexts. A subgroup of instructors ( n = 7) also participated in audio-recorded focus group meetings. Descriptive statistics were calculated for each survey item and the open-ended responses from the surveys and focus groups were analyzed qualitatively for major themes. The findings show that teachers had positive views of the SDS tasks' potential for speaking practice and diagnostic purposes, primarily in a flipped classroom model. Their perceptions seemed to be related to their own user experience and, in particular, to the perceived authenticity of a given task.